The CS detective : an algorithmic tale of crime, conspiracy, and computation - Kubica, Jeremy (San Francisco : No Starch Press, 2016)
"A mystery novel for computer science students and enthusiasts that introduces the concepts behind search algorithms and data structures. Each chapter teaches a new concept, ending with a technical explanation"--
Includes index.
Young Adult
Young Adult
Keywords: Algorithms -- Juvenile fiction; Computer science -- Juvenile fiction; Algorithms -- Fiction; Computer science -- Fiction; Algorithms -- Fiction; Computer science -- Fiction; Detective and mystery fiction